2012
DOI: 10.1186/1471-2377-12-81
|View full text |Cite
|
Sign up to set email alerts
|

The effects of levosimendan on brain metabolism during initial recovery from global transient ischaemia/hypoxia

Abstract: BackroundNeuroprotective strategies after cardiopulmonary resuscitation are currently the focus of experimental and clinical research. Levosimendan has been proposed as a promising drug candidate because of its cardioprotective properties, improved haemodynamic effects in vivo and reduced traumatic brain injury in vitro. The effects of levosimendan on brain metabolism during and after ischaemia/hypoxia are unknown.MethodsTransient cerebral ischaemia/hypoxia was induced in 30 male Wistar rats by bilateral commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
1
21
1
2
Order By: Relevance
“…However, findings in dogs indicated that levosimendan does not substantially penetrate the bloodbrain barrier in the healthy brain (48). A recent study using a bilateral common artery clamping and hypoxic ventilation for induction of cerebral ischemia indicated that only a low brain tissue concentration of levosimendan compared to serum concentrations can be achieved (49). No effects of levosimendan treatment on time course of lactate, glucose, pyruvate, and glutamate concentrations after transient ischemia were shown.…”
Section: Discussionmentioning
confidence: 95%
“…However, findings in dogs indicated that levosimendan does not substantially penetrate the bloodbrain barrier in the healthy brain (48). A recent study using a bilateral common artery clamping and hypoxic ventilation for induction of cerebral ischemia indicated that only a low brain tissue concentration of levosimendan compared to serum concentrations can be achieved (49). No effects of levosimendan treatment on time course of lactate, glucose, pyruvate, and glutamate concentrations after transient ischemia were shown.…”
Section: Discussionmentioning
confidence: 95%
“…Two recent studies examined the influence of forebrain hypoxia ischemia on autoregulation in the cerebral circulation (64,78). Acute impairments of autoregulation were reported within 60-90 min of reperfusion, suggesting a similar early disruption of cerebral autoregulation with this model of ischemia.…”
Section: Autoregulationmentioning
confidence: 99%
“…In fact, levosimendan has been shown to reduce cell death and inflammatory responses and improve function after transient ischemia of the spinal cord in rabbits [7,8]. While a dose-dependent protective effect in an in vitro model of traumatic brain injury could be demonstrated [9], levosimendan failed to improve brain metabolism or reduce glutamate release, inflammation and dysfunction of autoregulation in the initial phase after experimental global ischemic/hypoxic cerebral injury [10]. Its effect on focal transient ischemia has not been investigated in vivo in the brain as it has been in the heart [11].…”
Section: Introductionmentioning
confidence: 99%